IMPLEMENTATION OF THE WEB BASED PLATFORMS FOR COLLECTING AND FOOTPRINTING IP INFORMATION OF HOSTS IN THE COMPUTER NETWORK AND SYSTEMS: IMPLEMENTATION OF THE WEB BASED PLATFORMS FOR COLLECTING AND FOOTPRINTING IP INFORMATION OF HOSTS IN THE COMPUTER NETWORK AND SYSTEMS - Boyanov, Petar (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
In this paper implementation of the web based platforms for collecting and footprinting IP information of hosts in the computer network and systems is conducted. https://orcid.org/0000-0003-3668-6713